Facial Synthesis and Characterization of Polypyrrole/zinc oxide (ZnO) Nanorode and Flower-like Shape Composites - Nguyen Xuan, Sang (VNU Journal of Science: Mathematics - Physics, 2018)
Polypyrrole (PPy) nanocomposites reinforced with zinc oxide (ZnO) nanorod and nano flower were fabricated by chemical oxidative polymerization method using an ammonium per-sulphate (APS, (NH 4 ) 2 S 2 O 8 ) as an oxidizing agent. The polymer nanocomposite were characterized by X-ray diffractometer (XRD), scanning electron microscopy (SEM), and Fourier transform infrared (FTIR). The results were compared with pure as-prepared PPy. The SEM images of the nanocomposites show homogeneous dispersion characteristics and different morphologies of ZnO structures such as rod and flower-like shapes.  In the FTIR spectra, composite samples showed characteristic peaks of PPy shifted to higher positions confirmed the interfacial interactions between ZnO and PPy matrix.